Strategic Adaptation to Health-Tech Innovation: Challenges and Best Practices Among Private Hospitals in Nigeria - Alexandra Idaere Korubo-Fi (International Journal of Social Sciences and Management Research, 2026)
Health technology innovations, including telemedicine, electronic medical records, and mobile health platforms, are transforming patient care and operational management in Nigerian private hospitals. This conceptual study examines how private hospitals strategically adapt to health-tech innovations, identifying adoption barriers, leadership practices, and organizational mechanisms that facilitate successful integration. Drawing on dynamic capabilities theory, the study develops a conceptual framework linking health-tech adoption, strategic adaptation, leadership effectiveness, and organizational outcomes. Adoption challenges such as infrastructure limitations, regulatory uncertainty, and staff digital literacy are highlighted as critical factors that influence adaptation success. The framework emphasizes the mediating role of strategic adaptation in translating technological investments into improved patient care, operational efficiency, and competitive advantage. Managerial and policy implications are discussed, providing guidance for hospital leaders and regulatory authorities. The study contributes to health systems research by offering a holistic perspective on digital transformation in emerging healthcare markets and guiding future empirical investigations.